2019
DOI: 10.3390/d11110217
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Use on Bacterial Diversity and Community Structure in Temperate Pine and Indigenous Forest Soils

Abstract: Soil microbial communities are an important part of ecosystems that possess the capability to improve ecosystem services; however, several aspects of the ecology of forest soil bacterial communities are still unknown. Here, we investigated the impact of land-use change on soil bacterial communities and the soil characteristics. High-throughput sequencing was used to ascertain the bacterial diversity and canonical correspondence analysis was used to determine relationships between the bacterial communities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Similar to our finding, Navarrete et al (2015) reported higher abundance of phylum Actinobacteria in 57 soil metagenomic sets of sugarcane farms practicing straw retention. Other differentially significant phyla between forest and sugarcane farm samples were Planctomycetes, Firmicutes, Chloroflexi, Nitrospirae, and Armatimonadetes, that have been reported in other studies of forest and farmland soil ecosystems (Lauber et al, 2009;Shen et al, 2013;Cho et al, 2016;Amoo and Babalola, 2019). Indicator species analysis and bipartite association networks also provided insight into bacterial taxa, mainly, 12 OTUs associated to phylum Actinobacteria (mainly members of the order Frankiales, Acidimicrobiales, and Solirubrobacterales) that potentially drive the observed community structures in the sugarcane farm soil (Figure 5).…”
Section: Distribution Of Bacterial Taxa Across and Specific To Forestsupporting
confidence: 52%
See 1 more Smart Citation
“…Similar to our finding, Navarrete et al (2015) reported higher abundance of phylum Actinobacteria in 57 soil metagenomic sets of sugarcane farms practicing straw retention. Other differentially significant phyla between forest and sugarcane farm samples were Planctomycetes, Firmicutes, Chloroflexi, Nitrospirae, and Armatimonadetes, that have been reported in other studies of forest and farmland soil ecosystems (Lauber et al, 2009;Shen et al, 2013;Cho et al, 2016;Amoo and Babalola, 2019). Indicator species analysis and bipartite association networks also provided insight into bacterial taxa, mainly, 12 OTUs associated to phylum Actinobacteria (mainly members of the order Frankiales, Acidimicrobiales, and Solirubrobacterales) that potentially drive the observed community structures in the sugarcane farm soil (Figure 5).…”
Section: Distribution Of Bacterial Taxa Across and Specific To Forestsupporting
confidence: 52%
“…In this study, the clustering of forest topography type bacterial diversity was significant and negatively correlated with acidic pH. Several studies have reported that pH is one of the most important in environmental factors in shaping the biogeographical patterns of microbial diversity in forest ecosystems (Lauber et al, 2009;Shen et al, 2013;Cho et al, 2016;Amoo and Babalola, 2019). Hence, it can be concluded that ecological niche-based environmental filtering processes related to soil C and N contents including pH might play a dominant role in structuring bacterial communities along the different coastal scarp forest topographies.…”
Section: Forest Topography Type and Land Use Patterns Affects Soil Bamentioning
confidence: 50%
“…Bacteria are the most abundant microbes in the rhizosphere and are used as indicators of soil quality and fertility due to their rapid response to environmental alterations (Enagbonma et al 2020). The actions of bacteria are vital because they expedite most biogeochemical progressions, thereby influencing mineral nutrient availability in soils (Amoo and Babalola 2019). Rhizospheric bacterial communities can resist disease-causing pathogens, and promote tolerance to abiotic stressors, thereby promoting plant growth and development (Meena et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The commercial forest is presently on second rotation (one rotation = 30 years) and sustainable forest management is practiced. This plantation has been FSC certified for the past 20 years [1]. The indigenous forest and commercial plantation are about 2 km apart.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%